Increase the Speed Reading Ability Through Tracker-and-Method at SMA Negeri 2 Jeneponto - Nurul Ulfah; Muhammad Arief paturusi; Firman (English Language Teaching Methodology, 2023)
This study aims to improve students' speed reading skills by using the tracker- and-pacer method in SMA Negeri 2 Jeneponto, especially in grade XI Science 3.  The method used is tracker-and-pacer. The tracker-and-pacer method is a method of speed reading by using a pen or pen when reading. collect data by giving pre-test and post-test. the subjects of this study were students of grade XI science 3 as many as 30 students who took part in this study. based on the results of the study before being given treatment with the pre-test results by speed reading, none of the students managed to enter the good and very good categories. after being given treatment, the results of the post-test students experienced an increase of 6.7 very good, 53.3 good and adequate 40.0. The conclusion of this study is that the use of the tracker-and-pacer method in improving speed reading has increased.